Ethnomathematics on the Thomas Parr Monument of Bengkulu - Rahmat Jumri; Septia Agustina; Nyayu Masyita Ariani (MASI Mandiri Edukasi, 2025)
This research aims to identify mathematical objects in the building of Tugu Thomas Parr Bengkulu. The Thomas Parr Monument area is located on the coast of Bengkulu City. This research is descriptive qualitative research using an ethnographic approach. Data collection was done through observation, interview, and documentation. Data analysis techniques are done by collecting, reducing, presenting, and drawing conclusions. This research shows that the shapes of the Thomas Parr Monument Bengkulu building have mathematical concepts, including half circle, half sphere, rectangle, tube, congruence, and parallel lines. These results positively impact mathematics education because they can be used as a contextual learning medium through colonial heritage objects. Thus, the mathematical concepts in the Thomas Parr Bengkulu Monument can be used to introduce and understand geometric concepts through colonial heritage so that learning becomes more relevant, which can then be developed into teaching materials such as modules, LKPD, etc.